Research of the system-on-chip-based relay protection technology - Li, Xiaobo; Xi, Wei; Yu, Yang; Yao, Hao (Frontiers in Energy Research, 2023)
Relay protection device is the core equipment to ensure the safe and stable operation of power grid. With the open access of a large number of distributed generation, DC transmission and electric vehicles, a new deep low-carbon power system dominated by power electronic devices has gradually formed. The traditional control and protection architecture, methods and technology are difficult to meet the business characteristics and functional requirements of diversified interaction, agile response, safety and credibility of the power grid in the future. This paper presents a chip based relay protection technology based on system on chip, which is described from four aspects: the architecture design of relay protection SOC chip, software and hardware cooperative relay protection based on system on chip IP core, experimental verification and engineering application. The results show that the relay protection SOC chip proposed in this paper has significantly improved the performance of high-speed data acquisition and interaction through hardware algorithm engine acceleration and software and hardware collaborative computing, which is helpful to realize the local equipment operation and the integration of primary and secondary equipment, shorten the protection action time, and improve the speed, reliability and stability of relay protection devices.